Constraint Logic Programming Applied to the Resolution of a Problem of picking of Warehouse - Preissler Junior, Sigmundo; de Sá, Claudio Cesar; Sasse, Fernando Deeke (INFOCOMP Journal of Computer Science, 2008)
In this paper we apply logical programming with constraints to the problem of minimizing operational costs of a mobile agent that searches and moves objects in shelves, obeying a known physical configuration.